Several Factors Affecting the Occurrence of Audit Delay - Amin, Asbi (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This study aims to obtain empirical evidence regarding the effect of company size, solvency, company profit/loss, and KAP's reputation on audit delays in manufacturing companies listed on the Indonesia Stock Exchange. The population in this study were all manufacturing companies in the Food and Beverage Subsector, which were listed on the Indonesia Stock Exchange during the 2015-2017 period. The sample was selected based on the purposive sampling method. The selection of models used in this study were 12 companies. The data used in this study is secondary or quantitative, with data sources from financial reports audited by each company listed on the Indonesia Stock Exchange (IDX). The analytical method is the classical assumption test and multiple linear regression analysis. The study results show that company size, solvency, and KAP's reputation positively and significantly affect audit delay. In contrast, company profits/losses have a positive and insignificant impact on audit delay.